Biodiesel from alternative oilseed feedstocks: camelina and field pennycress. Issue 2 (March 2012) - Moser, Bryan R
Biodiesel is prepared from lipids by transesterification with a monohydric alcohol and may serve as a replacement or blend component for conventional petroleum diesel fuel (petrodiesel). Advantages of biodiesel over petrodiesel include strongly positive energy balance, domestic and renewable origin, enhanced lubricity and biodegradability, superior flash point, negligible sulfur and aromatics content, and low environmental toxicity. However, high feedstock cost, reduced storage and oxidative stability, inferior volumetric energy content and poor cold-flow properties represent critical technical deficiencies relative to petrodiesel. This review covers biodiesel standards, production and optimum reaction conditions, the influence of free fatty acids on production, the influence of composition on fuel properties and traditional feedstocks. A particular emphasis is placed on the alternative oilseed feedstocks camelina ( Camelina sativa ) and field pennycress ( Thlaspi arvense ) as promising nonfood candidates with high oil contents that would not displace existing agricultural production and would flourish in temperate climates.